Crosslinking catalytic hairpin assembly for high-contrast imaging of multiple mRNAs in living cells. Issue 27 (14th March 2019) - Huang, Du-Juan; Cao, Ting; Huang, Zhi-Mei; Wu, Zhenkun; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : A novel DNA nanotetrad mediated crosslinking catalytic hairpin assembly has been developed for high-contrast imaging of multiple mRNAs in living cells. Abstract : A novel DNA nanotetrad mediated crosslinking catalytic hairpin assembly (CCHA) is reported to generate clumps of cross-linked mesh products for high-contrast and simultaneous imaging of multiple mRNAs in living cells.